Alpha-band lateralization during auditory selective attention for brain–computer interface control. Issue 1 (2nd January 2018) - Spüler, Martin; Kurek, Simone
Abstract: In this paper, we investigated selective attention to auditory stimuli as a control mechanism for a Brain–Computer Interface (BCI). For BCIs using visual stimuli, the use of steady state or code modulated visual evoked potentials yields high performance. In this work, these approaches were transferred and tested in the auditory domain. The attentional modulation of code-modulated auditory evoked potentials (c-AEPs) and steady state auditory evoked potentials (SSAEPs) showed only a small effect, which is not sufficient for BCI control. However, for both kinds of stimuli, we found a spatial attention-related alpha-band lateralization that allows classification accuracies above 70% and thereby can be used for controlling a BCI.